2004
DOI: 10.1021/jp0486797
|View full text |Cite
|
Sign up to set email alerts
|

An ab Initio Study of Solid Nitromethane, HMX, RDX, and CL20:  Successes and Failures of DFT

Abstract: Using the PW91 and PBE density functional theories (DFT), we have studied four energetic molecular crystals: nitromethane, HMX, RDX, and CL20 with a wide range of basis sets. Our goal is to assess the accuracy of DFT when applied to organic molecular crystals (such as energetic materials) as scientists are beginning to include this methodology in energetic materials research without knowledge of the limitations of the method. Intramolecular distances, simple angles, and band gaps are converged at plane wave cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
122
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(142 citation statements)
references
References 25 publications
19
122
0
1
Order By: Relevance
“…Byrd et al studied a series of energetic materials at ambient pressure and found poor agreement with experiment, with errors as high as 9.6% for the calculation of lattice parameters. 21 A subsequent study demonstrated that an increase in pressure diminishes the importance of the dispersion interactions relative to the increasing contribution of the repulsive interactions. 22 As the external pressure applied to the simulation cell increased, the inaccuracies of the predicted intermolecular distances and lattice parameters relative to experimental data decreased, to the extent that good agreement with experiment was produced for pressures greater than 6-7 GPa.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Byrd et al studied a series of energetic materials at ambient pressure and found poor agreement with experiment, with errors as high as 9.6% for the calculation of lattice parameters. 21 A subsequent study demonstrated that an increase in pressure diminishes the importance of the dispersion interactions relative to the increasing contribution of the repulsive interactions. 22 As the external pressure applied to the simulation cell increased, the inaccuracies of the predicted intermolecular distances and lattice parameters relative to experimental data decreased, to the extent that good agreement with experiment was produced for pressures greater than 6-7 GPa.…”
mentioning
confidence: 98%
“…22 As the external pressure applied to the simulation cell increased, the inaccuracies of the predicted intermolecular distances and lattice parameters relative to experimental data decreased, to the extent that good agreement with experiment was produced for pressures greater than 6-7 GPa. 21,22 Shimojo et al 24 have shown that the dispersion correction implemented by Grimme 25 accounts for the dispersion interactions accurately for the -RDX crystal in the high-pressure regime (0 -15 GPa), while incurring little additional computational overhead. In addition, the authors determined that the non-empirical van der Waals density-functional (vdW-DF) method also provides an accurate description of the vdW interactions, but requires orders-of-magnitude more computational resource.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Heating due to each of these mechanisms depends on the histories of the states of local stress and rate of deformation in the material. Existing literature examines the behavior of energetic crystals and polymer-bonded explosives (PBXs) in two general forms: as single crystals with anisotropic material properties, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and as heterogeneous collections of energetic grains with isotropic material properties. [23][24][25][26][27] The single crystal simulations have been carried out using both discrete methods (e.g., molecular dynamics (MD) and density functional theory (DFT)) [6][7][8][9][10][11][12][13][14][15][16] and continuum scale methods.…”
Section: Introductionmentioning
confidence: 99%
“…Even in this case, the effort is computationally demanding and many approximations such as the tight-binding one must be used. Snap-shot density functional theory (DFT)calculations -instantaneous frozen atomic positions or limited time extend -have been performed on small models of Solid Nitromethane, HMX, RDX, and CL20 [7].…”
Section: Introductionmentioning
confidence: 99%